From JWH-018 to OXIZIDS: Structural Changes in Newly Emerged Synthetic Cannabinoids in the European Union from December 2008 to December 2021 - R. Andrews; R. Jorge; R. Christie; A. Gallegos (Emerging Trends in Drugs, Addictions, and Health)
Introduction: With new synthetic cannabinoids (SC) appearing on the European drug market every year, regional early warning systems are key to detect, monitor, and respond to the threats posed by them. The European Union Early Warning System (EU EWS) implemented by the EMCDDA started monitoring these substances in 2008. Since then, various national, European, and international drug controls have been implemented aiming at tackling these compounds. As a response, new SCs have appeared in the market containing structural moieties not covered by controls in place, increasing the diversity of substances and complexity of forensic analysis. Methods: All SCs under monitoring by the EMCDDA by the end of 2021 were organised according to their 4 structural elements: core, tail, linker, and linked groups. SC structural evolution has been analyzed in tandem with European and international legislation. Results: This study describes the structural evolution of SCs that have appeared in the EU, employing an in-depth analysis of the core, linker, linked and tail groups. This data has been compiled into tree maps and histograms, and a timeline displaying key structural milestones. Conclusions: SCs in Europe have diversified far from the original compound, JWH-018. This diversification has run in tandem with the introduction of legislation in a game of cat and mouse. The SC market is fast moving, with new structural groups appearing on the market less than 5 months after the introduction of a general SC ban in China.